Layer 2 VPN architectures - Luo, Wei (Cisco Press networking technology series., 2005)
"Layer 2 VPN Architectures is a comprehensive guide to consolidating network infrastructures and extending VPN services. The book opens by discussing Layer 2 VPN applications utilizing both AToM and L2TPv3 protocols and comparing Layer 3 versus Layer 2 provider-provisioned VPNs. In addition to describing the concepts related to Layer 2 VPNs, this book provides an extensive collection of case studies that show you how these technologies and architectures work. The case studies include both AToM and L2TPv3 and reveal real-world service provider and enterprise design problems and solutions with hands-on configuration examples and implementation details. The case studies include all Layer 2 technologies transported using AToM and L2TPv3 pseudowires, including Ethernet, Ethernet VLAN, HDLC, PPP, Frame Relay, ATM AAL5 and ATM cells, and advanced topics relevant to Layer 2 VPN deployment, such as QoS and scalability"--Resource description page.